Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1159/000502682
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil Treatment for Alzheimer’s Disease in Chronic Dialysis Patients

Abstract: Donepezil is one of the cholinesterase inhibitors that are indicated for the treatment of mild to moderate Alzheimer’s disease (AD). Pharmacokinetic analysis has shown that donepezil is primarily eliminated by renal excretion rather than biliary excretion in humans. Therefore, patients with impaired renal function are at high risk of toxicity caused by accumulation of this drug. It is also well known that dialysis patients have very often cholinergic disorders. On the other hand, with the increasing number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This review showed that cognitive impairment in older haemodialysis patients is positively correlated to mortality. Older haemodialysis patients are also at potential risk of being befalled with Alzheimer's disease, and receiving this diagnose is associated with an increased mortality [46,47]. Another study found that dementia was associated with an increased risk of death and dialysis drop out in adults aged over 75 years on dialysis [31].…”
Section: Discussionmentioning
confidence: 99%
“…This review showed that cognitive impairment in older haemodialysis patients is positively correlated to mortality. Older haemodialysis patients are also at potential risk of being befalled with Alzheimer's disease, and receiving this diagnose is associated with an increased mortality [46,47]. Another study found that dementia was associated with an increased risk of death and dialysis drop out in adults aged over 75 years on dialysis [31].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that cognitive function was improved best when the 5 mg daily dose was used, however, the plasma level came close to reaching a toxic level ( 39 ). Yiannopoulou et al, have reported a case series of five patients on maintenance HD with AD prescribed donepezil ( 40 ). They started with a dose of 2,5 mg daily and increased it after 1 month to 5 mg daily.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…They observed a slight improvement in cognitive and executive functions. During 10 years of follow up, the patients showed a mild cognitive decline per year for the first 5 years, which progressed to severe cognitive decline for the remaining years of follow up ( 40 ).…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…There is no recommended treatment to prevent cognitive decline in patients with kidney disease, and the few medications available for cognitive impairment have only modest effects (Yiannopoulou et al, 2019). There is a critical need to evaluate therapies to forestall cognitive impairment and maintain or improve cognitive function in older adults with CKD.…”
mentioning
confidence: 99%